A review on self-assembly in microfluidic devices. (16th October 2017) - Dou, Yingying; Wang, Bingsheng; Jin, Mingliang; Yu, Ying; Zhou, Guofu; Shui, Lingling
Abstract: Self-assembly is a process that operates over a vast range of length and time scales. Microfluidic technology has been proven to be a powerful tool to manipulate micro- and nano-scale substrates with precise control over size and speed using various fluidic materials and properties. In this review, we discuss the current status of microfluidic technology in manipulating fluid dynamics and interfacial phenomena which influence self-assembly process and resulted structures. The self-assembled materials/structures were summarized and discussed as the sequence of the objective size at the micro-, nano- and molecular scale. Overall, microfluidics is becoming a useful tool to manipulate various fluids regarding to physical and chemical properties, being inherently suitable for self-assembly process control.